Pengembangan Media Pembelajaran Berbasis Flip-Book digital Pada Subtema “Aku Anak Mandiri” di Kelas 3 Sekolah Dasar - Nopian, Mohammad Anggi; Ismatullah, Ismatullah; Dayurni, Popi (LPPM Universitas Bina Bangsa, 2025)
This research is motivated by the low use of digital learning media at SDN Ketileng 1, especially in thematic learning for grade III. Teachers tend to use lecture methods and textbooks, which cause students to be less active and get bored quickly. To overcome this, a digital Flip-Book-based learning media was developed on Theme 8 Subtheme 2